Exploratory study of electromyographic behavior of the vastus medialis and vastus lateralis at neuromuscular fatigue onset - Cristiano Rocha da Silva; Danilo de Oliveira Silva; Deisi Ferrari; Rúben de Faria Negrão Filho; Neri Alves; Fábio Mícolis de Azevedo (Universidade Estadual Paulista (UNESP), 2014)
This study aimed to determine and analyze the neuromuscular fatigue onset by median frequency (MDF) and the root mean square (RMS) behavior of an electromyographic signal (EMG). Eighteen healthy men with no prior knee problems initially performed three maximum voluntary isometric contractions (MVIC). After two days of MVIC test, participants performed a fatiguing protocol in which they performed submaximal knee-extension contractions at 20% and 70% MVIC held to exhaustion. The MDF and RMS values from the EMG signals were recorded from the vastus medialis (VM) and the vastus lateralis (VL). Analysis of the MDF and RMS behavior enabled identification of neuromuscular fatigue onset for VM and VL muscles in 20% and 70% loads. Alterations between the VM and VL in the neuromuscular fatigue onset, at 20% and 70% MVIC, were not significant. These findings suggest that the methodology proposal was capable of indicating minute differences sensible to alterations in the EMG signals, allowing identification of the moment when the MDF and the RMS showed significant changes in behavior. The methodology used was also a viable one for describing and identifying the neuromuscular fatigue onset by means of the analysis of EMG signals.